E-LEARNING DALAM PEMBELAJARAN MATA KULIAH PERENCANAAN DESAIN PEMBELAJARAN BAHASA ARAB PADA MAHASISWA PBA STAIN PAREPARE - Saepudin Saepudin (IAIN PAREPARE, 2015)
This research discuss the effectiveness of using e-learning to improve teaching and learning process on planning of the Arabic teaching design subject of seventh semester at Arabic Program STAIN Parepare. This research is classroom action research (CAR) based on revised Lewin Model by Elliot. The result of this research showed that using e-learning is effective to improve the teaching and learning process, namely the learning achievement is 77.9 more than the minimal criteria 75 and the students attitude is 87.5 as positive attitude and their participation is 61.3%. This data is better than the decided criteria.